Strategi Manajemen Keberlanjutan: Pendekatan Strategis Berbasis AI - Edy Awaludin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
In the digital era characterized by rapid technological advancements, artificial intelligence (AI) has emerged as a tool with the potential to transform the sustainability management paradigm. This research aims to explore how the application of AI, specifically generative artificial intelligence (GenAI), can influence sustainability management strategies across various industrial sectors. While AI offers opportunities to increase efficiency and productivity, challenges related to environmental impacts, particularly in the context of increasing energy consumption, remain a major concern. Data from the International Energy Agency (IEA) indicates that the information and communications technology (ICT) sector accounts for nearly 4% of total global energy consumption, and with the increasing use of GenAI, this figure is expected to continue to rise. This research also highlights the relationship between the use of GenAI tools and users' environmental perceptions and behaviors, indicating that the more frequently individuals use GenAI tools, the more they perceive the impacts of climate change. Therefore, it is crucial to raise awareness about the environmental impacts of everyday technologies. This research also discusses the importance of collaboration between the public and private sectors in creating a framework that supports the sustainable use of AI, as well as the need to support small and medium-sized enterprises (SMEs) in adopting this technology. By integrating sustainability considerations into the development and implementation of AI technology, we can contribute to global efforts to combat climate change and ensure that technological advancements do not come at the expense of our planet.